THE ROLE OF POSBINDU CADRES IN THE DETECTION OF HYPERTENSION IN THE WORKING AREA OF THE NUSA INDAH HEALTH CENTER BENGKULU CITY - Lissa Ervina; Della Yola Lestari; Wisuda Andeka Marleni (Poltekkes Kemenkes Bengkulu, 2023)
Hypertension is a non-communicable disease. Hypertension is a major problem in Indonesian society, its prevalence increases from year to year so that it becomes a serious problem. The role of cadres is needed in overcoming hypertension, cadres are formed to bridge health programs from health center to residents, therefore cadres have a very strategic role to disseminate health information. The purpose of this study was to determine how the role of posbindu cadres in hypertension detection in the working area of the Nusa Indah Health Center, Bengkulu City. This study uses qualitative research method with in-depth interview techniques. The method used in this research is a descriptive method used to examine a human group, an object, a condition, a system of thought, Informants in this study were 10 cadres as main informants and 2 health worker as supporting informants in the working area of health center Nusa Indah Bengkulu City. The results of this study can be concluded that the role of cadres that runs optimally is the role of cadres as coordinators and the role of cadres as actsivators. Cadres are not given responsibilities in accordance with the 5 tasks of the posbindu cadre role because there is no posbindu structure, cadres only assist posbindu activities but do not hold their respective roles. It is recommended that health service agencies divide cadre tasks according to the posbindu manual so that cadres can carry out their duties in accordance with the 5 roles of posbindu cadres.